Cysticercosis breast: a cytological diagnosis - Rajpoot, Jyoti; Arora, Sheetal; Gupta, Nikita; Arora, Rashmi (International Journal of Scientific Reports, 2018)
Parasitic lesions of breast are rare, usually seen in endemic areas. Clinically such cases are frequently misdiagnosed as benign or sometimes malignant tumors of breast. Cysticercosis is caused by larval form of Taenia solium, acquired via fecal oral route. Radiology may be suggestive of cysticerocosis. In our case, diagnosis was confirmed with fine needle aspiration cytology.